Directive Speech Acts in Cigarette Health Warning Labels: A Pragmatic Study - Ira Ferkhatul ' Aini; Avita Febriyani; Tatu Siti Rohbiah (CV. Ulil Albab Corp, 2026)
This study examines the use of directive speech acts in cigarette health warning labels circulated in Serang Regency, Banten, Indonesia. Drawing on pragmatic theory and Searle's speech act classification, this research employs a descriptive qualitative approach to analyze the types and functions of directive speech acts found in the warning texts. Data were collected from various cigarette brands available in local markets, minimarkets, and traditional shops. The analysis identifies five potential directive types—command, request, advice, warning, and prohibition—and investigates how these are linguistically realized. Findings reveal that all five analyzed warning texts are classified as warning (peringatan), realized through two primary strategies: (1) medical-fact-based warnings using direct causal statements linking smoking to specific diseases, and (2) personal-testimony-based warnings using first-person perspective to create an emotional and authentic effect. No other directive types were found in the data. These results indicate that cigarette health warning labels in the study area consistently employ a threat-based communication strategy designed to generate fear, vigilance, and health awareness among readers. The study contributes to the understanding of pragmatic functions in public health discourse.